ATP-dependent incorporation of 20S protease into the 26S complex that degrades proteins conjugated to ubiquitin. - Eytan, E (1989)
Previous studies have indicated that the ATP-dependent 26S protease complex that degrades proteins conjugated to ubiquitin is formed by the assembly of three factors in an ATP-requiring process. We now identify one of the factors as the 20S "multicatalytic" protease, a complex of low molecular weight subunits widely distributed in eukaryotic cells. Comparison of the subunit compositions of purified 20S and 26S complexes indicates that the former is an integral part of the latter. By the use of detergent treatment to activate latent protease activity, we show that the 20S protease becomes incorporated into the 26S complex in the ATP-dependent assembly process. It thus seems that the 20S protease is the "catalytic core" of the 26S complex of the ubiquitin proteolytic pathway.